KARAKTERISTIK PENGUNJUNG PADA OBJEK WISATA DANAU CIPOGAS KABUPATEN ROKAN HULU - Nurhidayah "; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Lake Cipogas tourist attraction Rokan Hulu regency is one of the tourist attractions that serve as excellent products in Rokan Hulu regency. Lake Cipogas will be developed into a new tourist attraction with attention to the characteristics of visitors. Therefore, for the development of tourist attraction on target, it is necessary to study the characteristics of visitors. This study aims to determine: (1) Characteristics of visitors who come to the tourist attraction Cipogas Lake Rokan Hulu; (2) The development efforts undertaken by the Department of Tourism and Culture of Rokan Hulu Regency according to the characteristics of visitors. This study uses quantitative methods with descriptive approach, the sample of research amounted to 100 respondents who are visitors who come to the Lake Cipogas tourist attraction Rokan Hulu regency. To determine the number of respondents researchers using accidental sampling technique, where researchers took the sample by chance found by chance while in the Lake Cipogas tourist attraction Rokan Hulu regency. Thus the researcher can know that the characteristics of visitors who come to the Lake Cipogas tourist attraction Rokan Hulu regency vary from the demographic and psychographic characteristics. Visitors who come dominated by female visitors and still a student / student status.Keywords: Characteristics, Visitors, Cipogas Lake, Tourist Attraction